Yazoo : Integration in a Deep-Southern Town - Morris, Willie (Book collections on Project MUSE., 2012)
In 1970 Brown v. Board of Education was sixteen years old, and fifteen years had passed since the Brown II mandate that schools integrate ""with all deliberate speed."" Still, after all this time, it was necessary for the U.S. Supreme Court to order thirty Mississippi school districts--whose speed had been anything but deliberate--to integrate immediately. One of these districts included Yazoo City, the hometown of writer Willie Morris. Installed productively on ""safe, sane Manhattan Island, "" Morris, though compelled to write about this pivotal moment, was reluctant to return to Yazoo and do.